2021
DOI: 10.1093/eurpub/ckab012
|View full text |Cite
|
Sign up to set email alerts
|

Healthy life expectancy by frailty state in Europe from 2004 to 2015: findings from SHARE

Abstract: Background As populations age, the possible consequences of increased frailty are a major concern for the health sector. Here, we investigate how life expectancy with and without frailty has changed during a 10–11-year-period across Europe. Methods The Sullivan method was used to investigate changes in life expectancy with and without frailty in 10 European countries. Frailty status (non-frail, pre-frail and frail) was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Frail older adults had a total LE reduction of 2.19 years and a reduction of robust LE of 3.87 years compared with robust older adults in China. These findings further confirm the previous findings that frailty can reduce LE [9][10][11][12]32] and the LE of older adults in the robust category [9][10][11][12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Frail older adults had a total LE reduction of 2.19 years and a reduction of robust LE of 3.87 years compared with robust older adults in China. These findings further confirm the previous findings that frailty can reduce LE [9][10][11][12]32] and the LE of older adults in the robust category [9][10][11][12].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the focus of this study, we found that the total LE of older adults at age 65 years in China was 14.74 years, which was lower than the LE of older adults in 10 European countries (16.4 years at age 70 years) [9], 15 European countries (21.4 years at age 65 years) [10], France (18.3 years for women and 14.8 years for men at age 70 years) [11], and Brazil (15.4 years at age 65 years) [12]. On average, older adults in China are expected to be in robust, pre-frail or frail status for 4.18, 7.46 or 3.10 years, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…An explanation could be that men in our sample had less physical and mental symptoms, less limitations in (I)ADL and less mobility problems. This might be a reflection of the evidence that a higher proportion of older European women are in a frail state [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sullivan method [ 28 ] was applied to calculate the HLE in patients with advanced schistosomiasis within each 5-year age interval based on life tables and disability data of patients [ 19 ]. This method is widely used in the estimation of HLE for its straightforward and succinctness [ 29 31 ]. In this study, HLE represents the schistosomiasis-free life expectancy for advanced cases.…”
Section: Methodsmentioning
confidence: 99%